Development of E-Modules in Geography Subject to Improve Self Regulation, Motivation and Learning Outcomes - Yenny, Novida; Delita, Fitra; Sidauruk, Tumiar; Elfayetti, Elfayetti; Herdi, Herdi (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
Mastery of learning technology by teachers is highly necessary for the digital era. For example, the ability of teachers to package learning materials using various software in various formats. One form of presenting learning materials with technology is an e-module. E-modules serve as the main teaching material in online learning and can also be used in face-to-face learning. The purpose of this study was to develop an -module, evaluate its feasibility and analyze its effect on motivation, self-regulation and learning outcomes in online learning. This research used the ADDIE model and then continued with a quasi-experimental research design with two pretest-posttest groups. The subjects of this study were students who participated in the Geography Learning Planning course. Class A (control group) and Class C (experimental group) students each consisted of 20 people. Data was collected through questionnaires and tests. The data analysis used is descriptive statistics and inferential statistics. The statistical tests carried out were t-test and ANCOVA by using SPSS version 24 software. The results showed that the e-module developed was very feasible and the application of the e-module in online learning was significantly increased self-regulation, motivation, and learning outcomes.